Smart System Resource Coordination Algorithm Based on 6G Technology. (9th May 2022) - Wang, Fang
Abstract : Most of the existing resource allocation algorithms do not take into account the restriction conditions such as the delay limitation of different services and the service volume requirements of different STAs. Moreover, the surge in the number of smart terminal devices has brought great challenges to the access effect of WLAN systems. Therefore, 6G technology will surely replace the current technology as the main means of future communication technology. This paper combines 6G technology to study the smart system resource coordination algorithm and analyzes the calculation process and actual effect of the algorithm. Moreover, this paper analyzes the coordination of smart system resources and verifies the effect of 6G technology in the coordination of smart system resources through experimental research. The results of experimental research show that the smart system resource coordination algorithm based on 6G technology can effectively improve the resource coordination effect of smart systems and has certain anti-interference, which will promote the construction of smart systems in the future.